Microfilament-mediated surface change in starfish oocytes in response to 1-methyladenine: implications for identifying the pathway and receptor sites for maturation-inducing hormones (The Rockefeller University Press, 1981)
Oocytes of the starfish Pisaster ochraceus exhibit an early response to 1-methyladenine (the maturation-inducing hormone), which is described for the first time. In this response approximately 6,500 spikelike surface projections, much larger than microvilli, emerge transiently from oocytes stripped of their follicle cells and then treated with the hormone in vitro. Each spike contains a prominent bundle of microfilaments, possibly composed of actin. The distribution of spikes when follicle cells are only partially removed and the morphological details of the normal junctional association between follicle cells and oocytes suggest that 1-methyladenine-sensitive sites (receptor sites) can be identified with the approximately 6,500 postjunctional specializations that are part of the oocyte surface. This finding in turn is employed to construct a set of hypotheses concerning the route that 1-methyladenine normally takes from the follicle cells to an oocyte during stimulation of maturation; it is postulated that, for each oocyte, 1-methyladenine is transported along approximately 6,500 thin follicle-cell processes, it is transmitted across the junctional gaps of an equivalent number of junctions between follicle cells and an oocyte, and then interacts with the postjunctional sites where 1- methyladenine receptors are thought to be clustered. Comparative aspects of this mode of intercellular communication are discussed.